Pengaruh Perbedaan Dosis Pakan Keong Mas Dan Ikan Rucah Pada Kepiting Bakau.(Scylla paramamosain) Terhadap Pertumbuhan dan Kelulushidupan Dengan Sistem Battery di Tambak Tugu, Semarang - Sadinar, Bintang; Samidjan, Istiyanto; Rachmawati, Diana (Journal of Aquaculture Management and Technology, 2013)
Mud crab is one of the marine living resources of high economic value, occupants biota type has been commercially cultivated in many tropical countries. Mud crabs are well known in the domestic market and abroad as a tasty meat flavor and high nutritional value which contains many important Nutrients such as minerals and fatty acids. The material used is a mud crab (Syilla paramamosain) with an average weight of 100 grams were 36 tails. The method used was experimental methods carried out in the field, using a completely randomized design (CRD). The treatment is given in the form of feeding snails with a dose of 3%, 5%, 7%, and 5% trash fish. Respectively for treatments A, B, C, and D, with 3 replications. The results showethat the dose of different feed snails provide a significant influence on the growth of absolute and specific growth rate of mangrove crabs, but give no significant effect on survival growth of mud crab. Mud crab highest absolute weight gained from treatment C (116.60±0.06 g), and then treatment D (112.67±0.471 g), treatment B (112.08±0.273 g), and the treatment of A (108.63±0.27 g), while the value of survival was 85.19%, 96.30%, 100%, and 85.19% , each on treatment A, B, C, and, D. Water quality are still in a decent range for maintenance of mud crab.